2016
DOI: 10.4018/978-1-5225-0125-1.ch014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Studying Tasks Compatibility with Tablets on Their Acceptance

Abstract: This chapter addresses the issue of tablets acceptance for studying. An experiment was carried out to test the effects of specific studying tasks experienced by students with no previous experiences with tablets on the perceived usability and usefulness of tablets. Students had to perform a high-compatible task (i.e. navigation/reading task) and a low-compatible task (i.e. writing task) for tablets. Subjective measures of usability, usefulness and use intention were designed to be more specific to the type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The primary objective of this research is to understand the factors that influence the adoption of VR technology, defined as customers' actual decisions to use VR (Gao & Krogstie, 2016). While adoption is the main focus, we also consider the concept of technology acceptance, defined as customers' willingness and intent to use VR (Amadieu et al, 2016), aiming for a comprehensive understanding of the customer adoption journey. These two concepts often overlap; for instance, the TAM (Davis et al, 1989) suggests that perceived ease of use and usefulness impact acceptance, which subsequently influences adoption behavior.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…The primary objective of this research is to understand the factors that influence the adoption of VR technology, defined as customers' actual decisions to use VR (Gao & Krogstie, 2016). While adoption is the main focus, we also consider the concept of technology acceptance, defined as customers' willingness and intent to use VR (Amadieu et al, 2016), aiming for a comprehensive understanding of the customer adoption journey. These two concepts often overlap; for instance, the TAM (Davis et al, 1989) suggests that perceived ease of use and usefulness impact acceptance, which subsequently influences adoption behavior.…”
Section: Literature Review and Conceptual Developmentmentioning
confidence: 99%
“…This was a strong limitation given that previous studies have shown the importance of taking into account the tasks performed by students. For example, for higher education students, Amadieu et al (2016) found that the perceptions of tablets became more positive after experiencing a reading-comprehension task of a multimedia document, while they became more negative after experiencing a writing task with the built-in digital keyboard. In this review, only Cacciamani et al (2018), Lin et al (2012), andMontrieux et al (2017) considered different types of use.…”
Section: Investigating the Impact Of Types Of Use And Learning Tasks On Perceptionsmentioning
confidence: 99%
“…While transferring learning and teaching from small-scale pilots to institution-wide implementation using mobile technology, it is important to consider some of the key issues in its implementation (Amadieu et al, 2016). For example, mobile technology can enable learners to escape from a typical classroom-learning environment to develop new and dynamic ways of learning.…”
Section: Different Uses Of Ict-based Learningmentioning
confidence: 99%
“…Their popularity kept on increasing and it is believed upcoming changes in education would be driven by TPC's which had enhanced the learning experience in educational settings (Kim and Frick, 2011). Therefore, it is pertinent to study their impact on learning outcomes (Johnson et al, 2014;Amadieu et al, 2016). Nguyen et al (2015) reported that the use of iPads enhanced a student's learning experiences however, better learning outcomes did not necessarily occur.…”
Section: Use Of Tpcs For Learningmentioning
confidence: 99%
See 1 more Smart Citation